PUBLIC AND PRIVATE HIGHER EDUCATION FINANCING IN NIGERIA - Ahmed, Sani (European Scientific Journal, ESJ, 2015)
In Nigeria, the demand for higher education is so high because education has been considered as not only an investment in human capital, but also a pre-requisite for economic development. The major source of fund to universities in Nigeria is the government proving about 90% of the total expenditure. Universities in Nigeria require a significant amount of funds to achieve their goals and objective, however, funds allocated to university education in Nigeria continue to be inadequate with the attendant effects of negative influences on the university system. The objective of the paper is to examine the present financial status of the universities to establish whether there is adequacy or inadequacy of funds to universities in Nigerian. The analysis is based on a secondary data and covers 2010-2011academic session and both descriptive and inferential statistic was used. The result reveals that university education is still not adequately funded to meet up with the international benchmark and best practice. The paper concludes that both private and public universities should intensify effort in revenue generation and also they should efficiently utilize the little resources available to them.